2016
DOI: 10.1021/acsami.6b11500
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Treated Lignin as Both Binder and Conductive Additive for Silicon Nanoparticle Composite Electrodes in Lithium-Ion Batteries

Abstract: This work demonstrates a high-performance and durable silicon nanoparticle-based negative electrode in which conventional polymer binder and carbon black additive are replaced with lignin. The mixture of silicon nanoparticles and lignin, a low cost, renewable, and widely available biopolymer, was coated on a copper substrate using the conventional slurry mixing and coating method and subsequently heat-treated to form the composite electrode. The composite electrode showed excellent electrochemical performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…Besides the water-soluble binders mentioned above, some NMP-based binders such as polyaniline (PANI) [16], poly(methyl methacrylate) (PMMA) [17], poly(vinylidenefluoride-co-hexafluoropropylene) (PVDF-HFP) [18], and sodium alginate functionalized with 3,4-propylenedioxythiophene-2,5-discarboxylic acid (SA-PProDOT) [19] for LFP cathode were also investigated. Apart from the above binders for LFP cathode, various novel binders including pectin [20], lignin [21], hyperbranched β-cyclodextrin…”
Section: Introductionmentioning
confidence: 99%
“…Besides the water-soluble binders mentioned above, some NMP-based binders such as polyaniline (PANI) [16], poly(methyl methacrylate) (PMMA) [17], poly(vinylidenefluoride-co-hexafluoropropylene) (PVDF-HFP) [18], and sodium alginate functionalized with 3,4-propylenedioxythiophene-2,5-discarboxylic acid (SA-PProDOT) [19] for LFP cathode were also investigated. Apart from the above binders for LFP cathode, various novel binders including pectin [20], lignin [21], hyperbranched β-cyclodextrin…”
Section: Introductionmentioning
confidence: 99%
“…Typical applications of lignin in (a–c) electrolytes and (d) binders and additives in electrode: (a) Synthesis of lignin‐PVP as a high‐performance and environment‐friendly gel polymer electrolyte for LIBs; (b) preparation route of lignin/LCP electrolyte membrane for high‐performance LIBs; (c) schematic of the lignin flow battery system assembly; (d) schematic illustration of the silicon‐lignin composite with lignin as both binder and conductive additive of silicon anode …”
Section: Preparation and Characterization Of Lignin‐derived Electrochmentioning
confidence: 81%
“…As shown in Fig. , lignin served as both binder and conductive additives for Si anode . It was found that the water‐soluble binder from lignin reduced the volume changes of Si anode during cycling .…”
Section: Preparation and Characterization Of Lignin‐derived Electrochmentioning
confidence: 99%
“…Lignin is also a promising starting substrate for the synthesis of carbonaceous materials for energy storage. [145][146][147][148][149][150][151][152] The morphology and/or type of lignin as substrate has generally an influence on the properties of the final product, even if the conversion is performed at high temperatures above 723 K. [148,[153][154][155][156][157][158][159] The electrochemical performance and stability of carbon-based materials, such as graphite or hard carbon, is mainly determined by the SEI, [160] that is, the decomposition layer separating the electrode from the liquid electrolyte that forms during first cycling. This general problem accounts for several electrode materials having a high theoretical capacity, such as Li 7 CuSi 2 with 1563 mA h g À1 , [161] but continuous SEI formation preventing their application.…”
Section: Current Collectorsmentioning
confidence: 99%